Effects of deficit irrigation and kaolin application on vegetative growth and fruit traits of two early ripening apple cultivars - Faghih, Somayeh; Zamani, Zabihollah; Fatahi, Reza; Liaghat, Abdolmajid (Biological research, 2019)
Background Drought is one of the main serious problems for agriculture production which its intensity is increasing in many parts of the world, hence, improving water use efficiency is a main goal for sustainable agriculture. Results Growth indices including relative shoot length growth (SL), relative stem diameter increase (SD) and relative trunk cross sectional area growth (TCSA) measured at the start and end of the season decreased by reducing the irrigation level. Chlorophyll index (CI) was decreased at 70% crop evapotranspiration, however water use efficiency (WUE), leaf and fruit total phenolic content (TPC), and fruit anthocyanin content (AC) were among the traits that showed increment by water deficit stress in both cultivars. Shafi-Abadi cultivar showed to be more sensitive to the water stress than ‘Golab’. Kaolin treatment improved SL, SD and CI traits, but this increase was statistically significant only for SD at 5% level. Kaolin had no significant effect on yield and water use efficiency (WUE), however, it had negative effect on yield efficiency (YE). Kaolin treatments also significantly increased fruit and leaf TPC ( P < 0.01) but had no effect on leaf and fruit total antioxidant activity (AA), as well as fruit anthocyanin content (AC) and soluble proteins (SP). Conclusions Irrigation at 85% ETc showed better results than 100% and 70% ETc levels for yield attributes. It seems that the more pronounced effect of kaolin on vegetative traits but not on the fruits, might be attributed to the early ripening and harvest time of the examined cultivars.